Proteinopathies - Pardayevna, Boriyeva Sohiba; Maksudovna, Shavkatova Nargis (American Journal of Biology and Natural Sciences, 2025)
This article provides information about proteinopathies - a group of diseases that result from the accumulation of misfolded or aggregated proteins in cells. The molecular mechanisms, main causes and pathological consequences of proteinopathies are reviewed. The most important proteinopathies, such as Alzheimer's, Parkinson's, amyloidosis and prion diseases, are also described, and their clinical features, diagnostics and potential treatment methods are analyzed. This article helps to form fundamental concepts of proteinopathies and study current research directions.